Nicht-Naives Erzählen. Folgen der Erzählkrise am Beispiel biografischer Schreibweisen bei Helmut Krausser - Lambrecht, Tobias (Deutsche Literatur. Studien und Quellen, 2018)
What is "naïve narrative" and to what extent should we regard it as obsolete? This study examines the poetological effects of the modern crisis in narration on German literature at the turn of the century based on the example of several novels by Helmut Krausser.